1999
DOI: 10.1021/ma990382x
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Polymerization of Acrylates by Zirconocene Complexes, an ab Initio and Density Functional Theory MO Study

Abstract: RHF/3-21G ab initio, density functional theory (B3LYP/3-21G), and single-point calculations using an effective core potential (B3LYP/6-31G*-ECP(S)//3-21G) are performed for different mechanisms of polymerization of acrylic acid and methyl acrylate by dicyclopentadienyl−zirconocene enolate complexes. Polymerization is considered involving a cationic zirconocene complex and a neutral zirconocene complex, respectively. In addition, a mechanism proposed by Collins is treated which involves a neutral and a cationic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…Results of the DFT calculation of acrylate polymerization suggest that late transition metal catalysts such as Ni or Pd polymerize the acrylate by the p-bond approach with migratory insertion [30] and early transition metal catalysts such as Zr polymerize the acrylate by the carbonyl oxygen lone pair approach with several intermediate steps. [31][32][33] Taking all these studies into consideration, it is reasonable to explain that the Zr(bbipy)Cl 2 /MAO system follows the carbonyl oxygen lone pair approach pathway (Scheme 3).…”
Section: Discussion On the Polymerization Mechanismmentioning
confidence: 99%
“…Results of the DFT calculation of acrylate polymerization suggest that late transition metal catalysts such as Ni or Pd polymerize the acrylate by the p-bond approach with migratory insertion [30] and early transition metal catalysts such as Zr polymerize the acrylate by the carbonyl oxygen lone pair approach with several intermediate steps. [31][32][33] Taking all these studies into consideration, it is reasonable to explain that the Zr(bbipy)Cl 2 /MAO system follows the carbonyl oxygen lone pair approach pathway (Scheme 3).…”
Section: Discussion On the Polymerization Mechanismmentioning
confidence: 99%
“…This is in agreement with the results of our theoretical calculations. [15] For such systems, these studies prefer a mechanism in which both a zirconocene cation and an enolate take part in chain growth. However, it is assumed that the applicability of this mechanism for controlling the stereospecificy of polymerization is only limited, since the location of C,C chain linkage occurs far from the metal centers.…”
Section: Structures Of Investigated Initiatorsmentioning
confidence: 99%
“…This is also shown by the arrangement of the reaction partners in the calculated transition state ( Figure 1). [15] Therefore, the structure of ligands should only play a minor role in the spatial orientation of the reaction partners.…”
Section: Structures Of Investigated Initiatorsmentioning
confidence: 99%
“…Me 3 SiCl (17.24 g, 158 mmol) was added within 1 h. The reaction mixture was allowed to warm up to room temperature and stirred for 12 h. The fine yellow precipitate was filtered off, washed with toluene and dried in vacuum (8.06 g (21 mmol), 70% yield). 1 4 ] were suspended at -78 8C in 80 mL toluene. The suspension was stirred and warmed to 20 8C within 30 min.…”
Section: Metallocenesmentioning
confidence: 99%
“…Sustmann et al performed theoretical calculations for the Collins mechanism and monometallic alternatives and found the lowest energy of activation for the propagation via the bimetallic mechanism. [4] Soga et al reported that cationic zirconocene complexes formed from dimethylzirconocenes and [Ph 3 C] [B(C 6 F 5 ) 4 ] or B(C 6 F 5 ) 3 polymerize MMA when activated with alkyl zinc or alkyl aluminum compounds. [5][6][7][8][9] Both, Collins and Soga, found two or three component catalysts for the polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%